2008
DOI: 10.1080/01674820701821047
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of labor course and women's sexuality in planned and unplanned pregnancy

Abstract: According to the results of this study, unplanned pregnancy has no adverse effect on parameters of the labor. The equal rate of partner's presence at delivery shows a high involvement of the partners of unmarried women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
1
6
1
Order By: Relevance
“…Perineal pain at 6 months after delivery was reported by 14% of the present cohort, a value that is in accordance with other studies [17,18]. This value does not differ from the reported incidence of perineal pain during pregnancy [19]. In the present study, the 2 women with a higher score of perineal pain had a minor skin duplicature that caused narrowing of the introitus and was easy to repair.…”
Section: Discussionsupporting
confidence: 92%
“…Perineal pain at 6 months after delivery was reported by 14% of the present cohort, a value that is in accordance with other studies [17,18]. This value does not differ from the reported incidence of perineal pain during pregnancy [19]. In the present study, the 2 women with a higher score of perineal pain had a minor skin duplicature that caused narrowing of the introitus and was easy to repair.…”
Section: Discussionsupporting
confidence: 92%
“…In his study, 15% of women actively asked about possible dysfunctions after birth and 15% of women actively asked about possible solutions to their health problems; in contrast to our study, in which only 8% of women did so [22]. At the same time, 53-83% experienced sexual problems that appear from 6 th weeks to 3 months after birth [22,25,26]. It is important to actively inquire about these problems because women themselves tend not to verbalize their problems [27].…”
Section: Discussioncontrasting
confidence: 44%
“…[21][22][23] Linear regression analysis showed that delay in initiation of coitus was linked to a shorter interval after CS than after episiotomy; while earlier initiation of coitus was associated with a shorter interval after SVD than after IVD. This relationship was, however, not significant.…”
Section: Discussionmentioning
confidence: 99%